Sustainability as a provocation to rethink management education: Building a progressive educative practice. Issue 4 (September 2014) - Kurucz, Elizabeth C; Colbert, Barry A; Marcus, Joel
An important aim of critical management education is to stand in critique of mainstream educative practice, while engaging in ideas of new possibility and proposals for alternative action. Opportunities for critique can be opened by identifying paradox or the appearance of contradiction in the imperatives underpinning conventional approaches to management and management education. One such contradiction is the "sustainability paradox": our dominant approaches to wealth creation degrades both the ecological systems and the social relationships upon which their very survival depends. In this article, we offer, from within a critical management education frame, an alternative vision of management education as a progressive educative practice: one that embraces our embeddedness in the natural world and our social relation to one another. We conclude with ideas for redirecting the contextual, organizational, curricular, and pedagogical dimensions of management education toward such a vision.